Synthetic access to 3,4-disubstituted pyroglutamates from tetramate derivatives from serine, allo-threonine and cysteine - Bagum, H; Christensen, KE; Genov, M; Pretsch, A; Pretsch, D; Moloney, MG (Elsevier, 2019)
A route allowing the conversion of substituted tetramates to 3,4-disubstituted pyroglutamates, making use of Suzuki coupling on an enol mesylate, followed by reduction, is both general and fully stereoselective.